Intervention non-adherence in a pragmatic randomized trial of a standardized order entry for colony stimulating factor prescribing. Issue 28 (1st October 2022) - Hershman, Dawn L.; Bansal, Aasthaa; Barlow, William E.; Arnold, Kathryn B.; Bell-Brown, Ari; Watabayashi, Kate; Kreizenbeck, Karma L.; Lyman, Gary H.; Sullivan, Sean D; Ramsey, Scott David
Abstract : 374 Background: Pragmatic trials evaluate the effectiveness of interventions in routine practice conditions. Pragmatic trials have high generalizability, but the treatment effect can be influenced by nonadherence to the intervention of interest. We conducted a pragmatic, cluster-randomized trial to test whether a guideline-based standing order entry (SOE) system improves use of primary prophylactic colony stimulating factor (PP-CSF) prescribing for patients receiving myelosuppressive chemotherapy. Clinics were assigned to the SOE or usual care. We investigated variability in adherence to the intervention. Methods: TrACER was a patient-informed, cluster randomized trial among 32 oncology clinics from the NCI Community Oncology Research Program. Clinics were randomized 3:1 to a guideline-based PP-CSF SOE or usual care (primary study). Among SOE intervention sites, automated orders for PP-CSF were included for regimens at high risk for febrile neutropenia (FN) and an alert not to use PP-CSF for low FN risk. A secondary 1:1 randomization assigned the 24 intervention sites to either SOE to prescribe or an alert to not prescribe PP-CSF for patients receiving intermediate FN risk-regimens. Providers were allowed to override the standing orders for individual patients. Results: Overall, 8 sites (659 patients) were randomized to usual care and 24 sites (2287 patients) to the intervention; 12 (1296 patients) were randomized to the intermediated risk SOE intervention and 12 (991 patients) to the alert not to prescribe PP-CSF. PP-CSF use among patients receiving high FN risk treatment was high and not different between arms (89.2% SOE; 95.8% usual care), however rates of PP-CSF use by site ranged from 48.6% to 100%. Among those receiving low FN risk regimens, PP-CSF use was low and not different between arms (6.3% SOE, 5.5% usual care), however PP-CSF use ranged from 0% to 19.4% across sites randomized to the alert to not prescribe. In the intermediate risk sub-study, PP-CSF was higher among sites randomized to SOE vs. the alert not to prescribe PP-CSF (37.1% vs 9.9%, OR = 5.91, 95% CI 1.77-19.70; p = 0.0038). However, there was considerable variability in adherence to intervention assignment: PP-CSF use ranged from 0% to 75% among sites randomized to SOE, and despite an alert to not prescribe, PP-CSF rates ranged among sites from 0% to 33%. FN rates were low and similar in both arms. Conclusions: In this randomized pragmatic trial aimed at improving PP-CSF prescribing, there was substantial variability in site adherence to the intervention assignment. While the ability to opt-out of the intervention is a feature of pragmatic trials, careful pre-study planning to estimate nonadherence is critical to ensure adequate power to detect an effect. Understanding reasons for intervention opt-outs will is also inform future pragmatic studies aimed at improving adherence to practice guidelines. Clinical trial information: NCT02728596.